New anthropometric classification scheme of preoperative nutritional status in children: a retrospective observational cohort study - Anne Stey; Joni Ricks-Oddie; Sheila Innis; Shawn J Rangel; R Lawrence Moss; Bruce L Hall; Albert Dibbins; Erik D Skarsgard (BMJ Publishing Group, 2018)
Objective WHO uses anthropometric classification scheme of childhood acute and chronic malnutrition based on low body mass index (BMI) ('wasting') and height for age ('stunting'), respectively. The goal of this study was to describe a novel two-axis nutritional classification scheme to (1) characterise nutritional profiles in children undergoing abdominal surgery and (2) characterise relationships between preoperative nutritional status and postoperative morbidity.Design This was a retrospective observational cohort study.Setting The setting was 50 hospitals caring for children in North America that participated in the American College of Surgeons National Surgical Quality Improvement Program Paediatric from 2011 to 2013.Participants Children >28 days who underwent major abdominal operations were identified.Interventions/main predictor The cohort of children was divided into five nutritional profile groups based on both BMI and height for age Z-scores: (1) underweight/short, (2) underweight/tall, (3) overweight/short, (4) overweight/tall and (5) non-outliers (controls).Main outcome measures Multiple variable logistic regressions were used to quantify the association between 30-day morbidity and nutritional profile groups while adjusting for procedure case mix, age and American Society of Anaesthesiologists class.Results A total of 39 520 cases distributed as follows: underweight/short (656, 2.2%); underweight/tall (252, 0.8%); overweight/short (733, 2.4%) and overweight/tall (1534, 5.1%). Regression analyses revealed increased adjusted odds of composite morbidity (35%) and reintervention events (75%) in the underweight/short group, while overweight/short patients had increased adjusted odds of composite morbidity and healthcare-associated infections (43%), and reintervention events (79%) compared with controls.Conclusion Stratification of preoperative nutritional status using a scheme incorporating both BMI and height for age is feasible. Further research is needed to validate this nutritional risk classification scheme for other surgical procedures in children.